Association between air pollution and hypertension hospitalizations: a time series analysis in Lanzhou - Anning Zhu; Miaoxin Liu; Jingze Yu; Runping Zhang; Yaoyi Zhang; Rentong Chen; Ye Ruan (BMC, 2024)
Abstract Background Air pollution is a major environmental risk factor. Hypertension is one of the most important modifiable risk factors for cardiovascular diseases. However, few studies have evaluated the impact of exposure to ambient air pollution on hypertension hospitalizations. Objective This study aims to explore the correlation between exposure to air pollution and hospital admissions for hypertension, to evaluate the short-term effects of air pollution on hypertension hospitalizations and its lag effects. Methods We collected air pollution concentration and hypertension hospitalization data from 2013 to 2020. Distributed lag non-linear models were employed to assess the impact of air pollution on hypertension hospitalizations in Lanzhou City. We also performed subgroup analyses and sensitivity analyses. Results A total of 47,884 cases of hypertension hospitalizations were included. Short-term exposure to NO2 and CO increased the risk of hypertension hospitalization. For each 10 µg/m3 increase in NO2 and each 1 mg/m3 increase in CO, the relative risk (RR) for hypertension hospitalization were highest at lag0-3 (RR: 1.0427; 95% CI: 1.0196, 1.0663) and lag3 (RR: 1.0986; 95% CI: 1.0350, 1.1661), respectively. SO2 at different lag structures showed opposite effects on hypertension hospitalization. O3 was significantly negatively associated with hypertension hospitalization. No correlation was observed between PM2.5 and PM10 and hypertension hospitalization. Females and individuals aged ≥ 65 were more susceptible to air pollution. The harmful effects of air pollution are greater in the cold season. Conclusion Short-term exposure to ambient air pollution increases risk of hypertension hospitalization.